No advantage of A beta 42-lowering NSAIDs for prevention of Alzheimer dementia in six pooled cohort studies. - Szekely, C A; Green, R C; Breitner, J C S; Østbye, T; Beiser, A S; Corrada, M M; Dodge, H H; Ganguli, M; Kawas, C H; Kuller, L H; Psaty, B M; Resnick, S M; et al. (Neurology, 2008)
INTRODUCTION: Observational studies show reduced incidence of Alzheimer dementia (AD) in users of nonsteroidal anti-inflammatory drugs (NSAIDs). One hypothesis holds that the subset of NSAIDs known as selective A beta(42)-lowering agents (SALAs) is responsible for this apparent reduction in AD risk. METHODS: We pooled individual-level data from six prospective studies to obtain a sufficient sample to examine AD risk in users of SALA vs non-SALA NSAIDs. RESULTS: Of 13,499 initially dementia-free participants (70,863 person-years), 820 developed incident AD. Users of NSAIDs (29.6%) showed reduced risk of AD (adjusted hazard ratio [aHR] 0.77, 95% CI 0.65-0.91). The point estimates were similar for SALAs (aHR 0.87, CI 0.72-1.04) and non-SALAs (aHR 0.75, CI 0.56-1.01). Because 573 NSAID users (14.5%) reported taking both a SALA and non-SALA, we examined their use alone and in combination. Resulting aHRs were 0.82 (CI 0.67-0.99) for SALA only, 0.60 (CI 0.40-0.90) for non-SALA only, and 0.87 (CI 0.57-1.33) for both NSAIDs (Wald test for differences, p = 0.32). The 40.7% of participants who used aspirin also showed reduced risk of AD, even when they used no other NSAIDs (aHR 0.78, CI 0.66-0.92). By contrast, there was no association with use of acetaminophen (aHR 0.93, CI 0.76-1.13). CONCLUSIONS: In this pooled dataset, nonsteroidal anti-inflammatory drug (NSAID) use reduced the risk of Alzheimer dementia (AD). However, there was no apparent advantage in AD risk reduction for the subset of NSAIDs shown to selectively lower A beta(42), suggesting that all conventional NSAIDs including aspirin have a similar protective effect in humans.
Keywords: Acetaminophen; Adolescent; Adult; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Analgesics, Non-Narcotic; Anti-Inflammatory Agents, Non-Steroidal; Aspirin; Cohort Studies; Female; Humans; Male; Middle Aged; Neuroprotective Agents; Peptide Fragments; Proportional Hazards Models; Prospective Studies; Risk Factors

NSAID use and dementia risk in the Cardiovascular Health Study: role of APOE and NSAID type. - Szekely, C A; Breitner, J C S; Fitzpatrick, A L; Rea, T D; Psaty, B M; Kuller, L H; Zandi, P P (Neurology, 2008)
BACKGROUND: Epidemiologic and laboratory studies suggest that nonsteroidal antiinflammatory drugs (NSAIDs) reduce risk of Alzheimer disease (AD). We therefore investigated the association between use of NSAIDs, aspirin, and the non-NSAID analgesic acetaminophen with incidence of dementia and AD. METHODS: Participants in the Cardiovascular Health Cognition Study included 3,229 individuals aged 65 or older, free of dementia at baseline, with information on medication use. We used Cox proportional hazards regression to estimate the association of medication use with incident all-cause dementia, AD, and vascular dementia (VaD). Additional analyses considered the NSAID-AD relationship as a function of age, presence of at least one epsilon 4 allele at APOE, race, and individual NSAIDs' reported ability to reduce production of the amyloid-beta peptide variant A beta(42). RESULTS: Use of NSAIDs was associated with a lower risk of dementia (adjusted hazard ratio or aHR 0.76, 95% CI or CI 0.60-0.96) and, in particular, AD (aHR 0.63, CI 0.45-0.88), but not VaD (aHR 0.92, CI 0.65-1.28). No similar trends were observed with acetaminophen (aHR 0.99, CI 0.79-1.24). Closer examination suggested AD risk reduction with NSAIDs only in participants having an APOE epsilon 4 allele (aHR 0.34, CI 0.18-0.65; aHR for others 0.88, CI 0.59-1.32). There was no advantage in AD risk reduction with NSAIDs reported to selectively reduce A beta(42). CONCLUSIONS: Results were consistent with previous cohort studies showing reduced risk of AD in NSAID users, but this association was found only in those with an APOE epsilon 4 allele, and there was no advantage for A beta(42)-lowering NSAIDs.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Anti-Inflammatory Agents, Non-Steroidal; Apolipoproteins E; Cardiovascular System; Dementia; Female; Humans; Incidence; Male; Proportional Hazards Models; Prospective Studies; Risk Factors